Dynamics of Arbuscular Mycorrhizal Fungi in the Rhizosphere of Medicinal Plants and Their Promotion on the Performance of Astragalus mongholicus - Wanyi Zhang; Chao He; Yuli Lin; Shenghui Qin; Duo Wang; Chunmiao Li; Min Li; Xiang Sun; Xueli He (Agronomy)
Arbuscular mycorrhizal fungi (AMF) act as intermediaries between the root systems of host plants and the surrounding soil, offering various benefits to medicinal plants, such as promoting growth and enhancing quality. However, the host range of AMF in medicinal plants and the characteristics of plant–AMF networks in farmland ecosystems remain insufficiently studied. In the present study, we measured AMF colonization, species diversity, and soil properties of 31 medicinal plants at the Anguo Medicine Planting Base in Northwest China. The medicinal plant–AMF network was subsequently analyzed, and the growth-promoting effects of AMF on Astragalus mongholicus were examined. Spore density, species richness, and total colonization exhibited significant variation across different medicinal plant species. Glomus melanosporum, G. claroideum, and Septoglomus constrictum were the dominant species among 61 AMF species. Soil organic matter, phosphatase, available nitrogen, and glomalin-related soil proteins (GRSPs) were the main factors affecting the AMF composition. Structural equation models and a variation partitioning analysis suggested a highly plant species-specific pattern of AMF distribution patterns, where the host identities explained 61.4% of changes in spore density and 48.2% of AMF colonization. The soil nutrient availability and phosphatase activity also influenced AMF colonization. Our results confirmed glomalin as an important contributor to the soil carbon in farmland for cultivating medicinal plants. The medicinal plant–AMF symbiotic network exhibited highly nested patterns, a low specialized structure, high connectance, and low modularity, which suggested saturated AMF colonization and symbiosis stability provided by redundant plant–AMF associations. Despite the wide host range among medicinal plants, AMF inoculation revealed species-specific effects on the growth performance and active ingredient content levels in A. mongholicus, G. claroideum and Sep. constrictum induced the highest biomass and active ingredient content accumulation in A. mongholicus. These findings advance our understanding of AMF community dynamics in the rhizosphere of medicinal plants and offer valuable insights for optimizing medicinal plant cultivation practices.